Some psychological studies of high risk sports - Kajtna, Tanja (Kinesiologia Slovenica, 2004)
This article attempts to present some psychological studies of high risk sports and athletes that engage in them on a top level. We define high risk sports as "any sport where one has to accept a possibility of severe injury or death as an inherent part of the activity" (Breivik, 1995), the reviewed studies present the personality and sensation seeking characteristics of high risk sports athletes. We define the sports that can be classified into this category of sports, deal with the term used to describe these sports, and also present the findings of existing international studies of these sports and two studies conducted on Slovene sample. In addition, we present which findings are confirmed by several studies (the most common finding is that high risk sports athletes are high sensation seekers and most studies find them to be extraverted) and which findings are contradictory (contradictions ofen refer to whether we can study all high risk sports athletes as a homogenous group or should rather separate them according to specific sports). We also elaborate on methodological aspects (low number of participants, few studies with female participants) of the reviewed studies and some other problems, and suggest some aspects for further research.
Keywords: ekstremni športi; osebnost; psihologija športa; rizični športi; šport; športniki